Evaluation of a program to teach health professionals to search MEDLINE. - Starr, S S (1987)
This study analyzes the search behavior of end users who had taken a class in searching MEDLINE on the National Library of Medicine's MEDLARS system. Of the class alumni, 58% obtained passwords. Most of these were still conducting their own searches twelve to eighteen months later. Telephone interviews and search observations indicated that these end users were satisfied with their results and felt they had mastered the basic mechanics of searching. However, appropriate use of explodes and subheadings, as well as locating appropriate search terms, still presented difficulties for them. Further training in these areas may be required.